Potential of using burning equipment in the engineering company and metallurgy - Schindlerová, Vladimíra; Bučko, Michal; Šajdlerová, Ivana (Manufacturing Technology Journal, 2020)
Currently, companies have been trying to make the use of their technology, manufacturing capabilities and experienced workforce to respond flexibly to market demands. Collecting and processing of all relevant data in the company is one of the key points to which increased attention should be paid so as to maximize the efficient use of own resources and consequently ensure a continuous reduction of pro-duction costs. The article deals with the use of burning machines in engineering company. The product range involves the production of burnouts from standard and special materials as well as welded steel parts of structures. The company has long struggled to optimize the material and information flow between particular production operations. This paper was focused on information flow logistics, which proved to be the biggest weakness of the central material preparation department during the bottleneck analysis. The scientific contribution of the resolved issue can be seen mainly in the possibility of inter-connecting process analysis and optimization of material and information flows.
Keywords: Optimization; Information system; Burning machine; Production process; Process analysis